Pemanfaatan Argumen dalam Teks Diskusi pada BSE Bahasa Indonesia Kelas IX SMP: Media Pengembangan Kreativitas - Anggraini, Dwi; Syafi'i, Imam (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2021)
This study aims to determine the use of the arguments contained in the discussion text in the BSE Indonesian Language textbook for class IX SMP, both in supporting and challenging arguments. This study uses a qualitative descriptive approach with content analysis method. Sources of data in this study are a number of discussion texts contained in the discussion text material in the BSE Indonesian Language textbook for class XI SMP. The results of this study indicate that the supporting and challenging arguments in the discussion text 1 under the title "Recycling for a Green Lifestyle" have a good rating category in the completeness of the content and pouring out the problems/issues discussed. Meanwhile, in supporting and challenging arguments, discussion text 2 under the title “Awareness of Paying Taxes” has a very good assessment in the completeness of the content and discussion of the problems/issues discussed. So that this discussion text book is able to become a learning material that can increase the creativity of students in utilizing the arguments described in the discussion text.Keywords: Discussion Text, Supporting Arguments, Challenging Arguments